The social world of Jesus and the Gospels - Malina, Bruce J. (London ; New York : Routledge, 1996)
In order to interpret historical writings, readers must not employ their modern understanding of the world, but must strive to grasp the perceptions and social contexts of the original audience. The goal of this collection of essays to assist the twentieth-century New Testament reader in understanding the meaning of the New Testament, and to provide the reader with a set of workable scenarios for reading the New Testament: How did first-century persons think about themselves and others? Did they think Jesus was a charismatic leader? Why did they call God "Father"? Were they concerned with their gender roles?
1. Reading Theory Perspectives -- 2. First-Century Mediterranean Persons: A Preliminary View -- 3. The Mediterranean Self: A Social Psychological Model -- 4. Mary and Jesus: Mediterranean Mother and Son -- 5. Was Jesus a Charismatic Leader? -- 6. Patron and Client: The Analogy Behind Synoptic Theology -- 7. Christ and Time: Swiss or Mediterranean? -- 8. The Received View and What It Cannot Do.
Includes bibliographical references and indexes.
Keywords: Bible. -- Social scientific criticism; Sociology, Biblical; Jews -- Social life and customs -- To 70 A.D.; Palestine -- Social life and customs -- To 70 A.D.